2009
DOI: 10.1007/s12598-009-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of acid dissolved titanium slag from Australia by sodium hydroxide

Abstract: The kinetics of the decomposition of acid dissolved titanium slag with a sodium hydroxide system under atmospheric pressure was studied. The effect of reaction temperature, particle size and NaOH-to-slag mass ratio on titanium extraction was investigated. The results show that temperature and particle size have significant influence on titanium extraction. The experimental data of titanium extraction show that the shrinking core model with chemical reaction controlled process is most applicable for the decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…The apparent activation energy of titanium conversion in NaOH-KOH is calculated to be E = 43.1 kJ/mol, which is much lower than that of Ti-slag decomposed in molten NaOH system (62.4 kJ/mol). 7 3.3. Water Leaching Process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent activation energy of titanium conversion in NaOH-KOH is calculated to be E = 43.1 kJ/mol, which is much lower than that of Ti-slag decomposed in molten NaOH system (62.4 kJ/mol). 7 3.3. Water Leaching Process.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 TiO 2 rutile white pigment with good pigmentary properties was prepared via the new method. 8 A demonstration plant has been built in Shandong Province, which has approached zero emission of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes treatment of ilmenite or its slag with alkali salts (Na and K) for high grade TiO 2 preparation was carried [4,[15][16][17][18][19][20]. Other investigators indicated that titanium ores can be treated with alkali salts followed by acid (H 2 SO 4 or HCl) attack for titania preparation [17,19,[21][22][23]. The present work aims to prepare pure titania sample via intermediate product produced from slag roasting process with Na 2 CO 3 using H 2 SO 4 acid solution.…”
Section: Introductionmentioning
confidence: 99%
“…So it is of high comprehensive utilization value . It is estimated that the yield of vanadium coming from vanadium–titanium magnetite is close to 88% each year and many studies were focused on preparing TiCl 4 , Ti‐rich material, and so on by using titanium slag. As the phase composition of high chromium vanadium–titanium magnetite is more complex than ordinary vanadium–titanium magnetite, the processes of agglomeration, blast furnace smelting, and comprehensive utilization are more difficult.…”
Section: Introductionmentioning
confidence: 99%